INDUSTRI ANIMASI MENJADI TUAN DI RUMAH SENDIRI (Sebuah Kenyataan dan Harapan bagi Insan dan Penggiat Industri Animasi Lokal) - -, Handriyotopo (Seni Media Rekam ISI Surakarta, 2015)
One day animation industry in Indonesia can be host of his own country. An expectation that requires a struggle and a challenge to the invasion of the animated movie from outside of the domestic animation industry. A lot of animated film produced by the global industries require human resources and no small cost. In fact, the capability of Indonesian human resources in animation are not inferior to the foreign and a lot of Indonesia human resources involved in global animation industry such as Hollywood industry. There are domestic animation industries which produce animation movie, but they are not consumed for domestic people of Indonesia. Government support is expected to develop the domestic animation industry, in which the development of creative industries have promising prospects for increasing foreign exchange earnings. Internet and social media are media to introduce and promote the Indonesia animated films to the international markets although they are still based on local identity.Keywords: animation, creative, local, and identity